Assessing the Islamic Bank Financing During Economic Recession: The Role of Stimulus Regulation POJK Number 11/POJK.03/2020 - Ririn Riani; Ries Wulandari (AL-MUZARA'AH, 2022)
This study examines the role of the POJK stimulus policy No. 11/POJK.03/2020 on the decision of financing in Indonesia Islamic banking. Furthermore, the study aims to be able to assess the financing behavior of Islamic banks. Accordingly, we design a quantitative approach with panel data analysis method. With case studies on 12 Islamic Commercial Banks with a time period from quarter 1-2017 to quarter 4-2020. We found that the total financing of Islamic banks experience significant changes after the period of economic recession that hit Indonesia. Then, the study found that the role of stimulus regulation has a positive and significant effect on the distribution of total bank financing. This shows that the stimulus regulation through financing relaxation or financing restructuring does not prevent banks from continuing to channel financing to the public. This study also found that Islamic banks do not behave pro-cyclicality behavior towards the business cycle.